Something happened in our town : A child's story about racial injustice - Celano, Marianne; Green, Leslie (Chicago : BG Records, 2019)
Following a police shooting, two families?one White and one Black?discuss the event, its aftermath, and what they can do to help.
Unabridged.
Narrator: Leslie Green.
AD540L
Requires OverDrive Listen (file size: N/A KB) or OverDrive app (file size: 20006 KB).
K-3.
SORA audiobook.
Keywords: Electronic books; Racism; Prejudices -- Juvenile fiction; Police shootings -- Juvenile fiction; Racism -- Fiction; Prejudices -- Ficton; Police shootings -- Fiction; SORA audiobook